Devising the technology for thickening and dehydration of activated sludge from municipal treatment plants in sedimentation centrifuges - Shkop, Andrii; Shestopalov, Oleksіi; Bosiuk, Alona; Abramova, Alla; Titov, Andrii; Romanchyk, Andriі (Technology center PC, 2025)
The object of this study is the process of thickening and dewatering excess activated sludge from municipal wastewater treatment plants in sedimentation centrifuges. The subject of the study is the conditions and factors that affect the efficiency of sludge dewatering, taking into account environmental safety, energy efficiency, and the possibility of reusing resources. The study is aimed at solving the problem of the efficiency and environmental safety of dewatering excess activated sludge. The results of studies on the centrifugation of samples of excess and stabilized activated sludge in a laboratory centrifuge showed that effective separation into sediment and clarified liquid is achieved at a separation factor of 200–600 with the use of a flocculant. In an industrial centrifuge under a flow mode, the best results were obtained at a separation factor of 450 and a flow rate of 9.4 m3/h: the solid phase content in the thickened product was 12.8 g/l, at an input concentration of 4.2 g/l and the residual in the clarified liquid – 0.3 g/l. The proposed scheme for thickening and dewatering sludge stabilizes the process and improves the quality of the product for further use or disposal. For effective dewatering, mixing the thickened sludge with thickened activated sludge is recommended due to the need for a mineral component. It has been established that thickening of activated sludge is possible using centrifuges in a weak centrifugal field (Fr = 200–600), with a cationic flocculant consumption of 5 kg/t. The second stage – dehydration – is implemented using sedimentation centrifuges. The results could be used at municipal treatment plants to optimize the processes of thickening and dewatering of excess activated sludge, taking into account energy efficiency and environmental safety. The proposed centrifuge operating modes and the technological scheme enable process stability, reduce sludge volumes, and improve the quality of the final product for further use or disposal.
Keywords: activated sludge; activated sludge dewatering; centrifugal units; thickening of excess sludge; environmental safety; fermented sludge; stabilized sludge